2014
DOI: 10.1136/emermed-2013-203451
|View full text |Cite
|
Sign up to set email alerts
|

Do difficulties in accessing in-hours primary care predict higher use of out-of-hours GP services? Evidence from an English National Patient Survey

Abstract: IntroductionIt is believed that some patients are more likely to use out-of-hours primary care services because of difficulties in accessing in-hours care, but substantial evidence about any such association is missing.MethodsWe analysed data from 567 049 respondents to the 2011/2012 English General Practice Patient Survey who reported at least one in-hours primary care consultation in the preceding 6 months. Of those respondents, 7% also reported using out-of-hours primary care. We used logistic regression to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 16 publications
3
35
0
1
Order By: Relevance
“…The absence of an increase in attendance in accident and emergency departments or in use of out-of-hours GP services after introduction of either GP triage or nurse triage suggests that triage is not regarded as a suffi cient barrier that could result in patients seeking care outside of their practice; 26 nor does easier access to telephone advice in general practice seem to reduce patient contacts in other settings. Introduction of nurse triage was associated with a reduction in overall patient satisfaction, but more substantial reductions in some individual components of satisfaction were suggestive of patients' experience of care.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of an increase in attendance in accident and emergency departments or in use of out-of-hours GP services after introduction of either GP triage or nurse triage suggests that triage is not regarded as a suffi cient barrier that could result in patients seeking care outside of their practice; 26 nor does easier access to telephone advice in general practice seem to reduce patient contacts in other settings. Introduction of nurse triage was associated with a reduction in overall patient satisfaction, but more substantial reductions in some individual components of satisfaction were suggestive of patients' experience of care.…”
Section: Discussionmentioning
confidence: 99%
“…29 Several of these access questions have been used in other research as proxies for markers of patient access to surgery, although the composite access score has not yet been used as a research tool. [18][19][20][21][22][23][24] Further independent variables that have been shown to be associated with variation in practice-level performance in previous studies in English primary care were identified. These were: the size of the practice measured in numbers of patients in 2010; and the GP Practice Index of Multiple Deprivation (IMD 2010, rank), which is estimated by taking a weighted average of the IMD scores for each Lower Super Output Area (LSOA) in which a given practice has registrations.…”
Section: Methodsmentioning
confidence: 99%
“…27 The dependent variable was the rate of emergency admissions for asthma per 1000 patients on the asthma register, for each general practice. The codes for emergency admission were the PBR tariff 21,22,23,24,28; the ICD-10 primary diagnoses codes for asthma were J45-J46.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 For example, difficulties in accessing in-hours care are known to predict higher use of primary care OOH services. 16 This study explored the experiences, views, and opinions of patients with cancer and their caregivers who had used an OOH primary care service for assistance with pain management. Interviews explored the circumstances prompting OOH contacts relating to pain, experiences of daytime care, and participants' experiences of using OOH primary care services for help with cancer pain management.…”
Section: Introductionmentioning
confidence: 99%